Effective strategies and practical implementation in teaching english to deaf students: Insights from a qualitative case study of communication approaches and learning media - Ningsih, Ayu Puspita; Purnama, Yulian; Wahidiyati, Irra (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Deafness is a condition when a person cannot hear, either partially or completely. Deaf students have different ways of communicating with other people, including the way they learn things. Teachers need to use special methods in teaching deaf students so that the objectives of the teaching and learning process can be achieved. This research aims to identify the strategies used by teachers in teaching English to deaf students and find out how these strategies are implemented. Methods: This research uses a qualitative descriptive method and is based on a case study at SMPLB Karya Bakti Don Bosco Wonosobo (Special School for the Deaf). To find answers to these problems, this study interviewed an English teacher about the strategies implemented during the learning process in the classroom. To obtain more in-depth data, researchers also conducted classroom observations. Findings: This research shows that teachers use sign language strategies, read lips and use various media. As for the implementation of this strategy, the teacher focuses more on enriching students' vocabulary, the teacher speaks slowly and clearly when using sign language. teachers teach simple conversations; teachers use varied media. Conclusion: Teaching English to deaf students requires tailored strategies such as sign language, lip-reading, and media use, which must be implemented with patience and persistence to support effective learning. Novelty/Originality of this article: The findings in this study emphasize the fact that teaching deaf students requires excessive effort and great persistence, and the strategies presented in this study can be useful for other English teachers teaching deaf students.